Deciphering Oxidative Stress in Cardiovascular Disease Progression: A Blueprint for Mechanistic Understanding and Therapeutic Innovation - Zhaoshan Zhang; Jiawei Guo (Antioxidants)
Oxidative stress plays a pivotal role in the pathogenesis and progression of cardiovascular diseases (CVDs). This review focuses on the signaling pathways of oxidative stress during the development of CVDs, delving into the molecular regulatory networks underlying oxidative stress in various disease stages, particularly apoptosis, inflammation, fibrosis, and metabolic imbalance. By examining the dual roles of oxidative stress and the influences of sex differences on oxidative stress levels and cardiovascular disease susceptibility, this study offers a comprehensive understanding of the pathogenesis of cardiovascular diseases. The study integrates key findings from current research in three comprehensive ways. First, it outlines the major CVDs associated with oxidative stress and their respective signaling pathways, emphasizing oxidative stress’s central role in cardiovascular pathology. Second, it summarizes the cardiovascular protective effects, mechanisms of action, and animal models of various antioxidants, offering insights into future drug development. Third, it discusses the applications, advantages, limitations, and potential molecular targets of gene therapy in CVDs, providing a foundation for novel therapeutic strategies. These tables underscore the systematic and integrative nature of this study while offering a theoretical basis for precision treatment for CVDs. A major contribution of this study is the systematic review of the differential effects of oxidative stress across different stages of CVDs, in addition to the proposal of innovative, multi-level intervention strategies, which open new avenues for precision treatment of the cardiovascular system.